Otters - Miller, Sara Swan. (New York : PowerKids Press, 2008)
Explores the physical characteristics, habitat, and behaviors of otters, and examines the methods that are taken in order to protect their habitat.
Includes index.
3.1
K-3
Keywords: Otters -- Juvenile literature; Otters; Otters; Otters